PENGARUH IKLIM ORGANISASI TERHADAP PRESTASI KERJA PEGAWAI PADA SEKRETARIAT DAERAH KABUPATEN HALMAHERA TENGAH - UMASANGADJI, FATMAWATI; LENGKONG, FLORENCE DAICY; OGOTAN, MARTHA (JURNAL ADMINISTRASI PUBLIK, 2014)
This researchmoved from themain problems, namely: the extent to which organizationalclimate on the performanceof employeesat the District Secretariatof Central Halmahera. Thus, thisresearchaims: toanalyze the influence oforganizational climateon the performanceof employeesat the DistrictSecretariatof Central Halmahera.This study uses aquantitative approach to the application of descriptive and explanatory. Andinformation collected through questionnaires distributed to the technique 72 respondents, and is equippedwith observation and documentation techniques, and then analyzed by applying a frequency table analysistechnique, the product moment correlation and simple linear regression.Based on the analysisof data, it is known that: the results of a descriptive analysis of the technique ofanalysis tables (frequency tables) it is known that the distribution of respondents' answers to theOrganizational Climate variables are in the category of "medium" to "low", but the dominant categorized"moderate" or medium with mean average performance of 56.09%, while the performance varies frommoderateto high,but it tends to be inthe category of "moderate" with an average performance of 69.40%.Thus, it can be concluded that the Organization Climate has the positive and significant effecton theperformance of employees and are contributive. This means that it is empirically Climate organizationscontribute significantly and substantially to the work performance of employees, particularly at the RegionalSecretary (Secda) of Central Halmahera.Keywords: Organizational Climate, Employee Job Performance